Ultrasonographic findings of placental abruption observed on superb microvascular imaging - Reiko Suzuki; Natsumi Furuya; Junichi Hasegawa; Chika Homma; Yuriko Iwahata; Nao Suzuki (Elsevier, 2022)
Objective: To demonstrate ultrasound pathological findings of placental abruption (PA) detected using a new Doppler method: superb microvascular imaging (SMI). Case report: The patient was a pregnant woman with dark brown vaginal discharge at 32 + 4 weeks of gestation. Conventional ultrasound revealed an exophytic heterogeneous area measuring 3 cm, between the placenta and myometrium. SMI showed no minor blood flow inside the area. A diagnosis of marginal sub-chorionic hematoma was made. On the seventh day of hospitalization, SMI showed pulsation of blood flow in the inter-villous space and fetal blood flow in the villous trees. Due to an increase in the frequency of uterine contractions, an emergency cesarean section was performed. Histopathological examination showed hematomas beneath the decidual tissue, and the decidual layer was undamaged. The inter-villous space was preserved. Conclusion: SMI can contribute to a more accurate PA diagnosis that may lead to timely administration of obstetric intervention.